1997
DOI: 10.3758/bf03210783
|View full text |Cite
|
Sign up to set email alerts
|

Preference for familiar humans by rats

Abstract: Many "higher" animals are commonly assumed to distinguish between individual humans. This belief is based largely on anecdotal reports; in reality, there is little empirical evidence to support human recognition in nonhuman species. Wereport that laboratory rats consistently chose a familiar human over an unfamiliar human following fourteen and five IO-min exposures and even following a single IO-min exposure. Furthermore, this preference was retained in the absence of additional contact for at least 5 months.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 15 publications
3
21
0
1
Order By: Relevance
“…Rats took less time to approach, spent more time interacting with, and produced more 50-kHz USV in the presence of, the familiar than the unfamiliar hand, consistent with a previous report that rats prefer familiar compared to unfamiliar humans (Davis et al, 1997). They were less active in the presence of the familiar hand, probably because they spent more time near the hand rather than moving around the box.…”
Section: Effects Of Handling Experiencesupporting
confidence: 87%
“…Rats took less time to approach, spent more time interacting with, and produced more 50-kHz USV in the presence of, the familiar than the unfamiliar hand, consistent with a previous report that rats prefer familiar compared to unfamiliar humans (Davis et al, 1997). They were less active in the presence of the familiar hand, probably because they spent more time near the hand rather than moving around the box.…”
Section: Effects Of Handling Experiencesupporting
confidence: 87%
“…Although both gentling programs were able to achieve a similar "taming" effect, the duration of the effect was dependent on how the gentling program was executed. A long-term effect similar to the one observed with the "intensive" gentling program was also reported by Davis et al (1997): In this study, adult rats, that were accustomed to daily handling, were petted for 10 minutes a day by the same person for 14 days and fed treats. The rats recognized the person who had gentled them and preferred her over an unfamiliar person.…”
Section: Tablesupporting
confidence: 74%
“…In addition, it was shown that rats are able to distinguish between different people, and that they prefer familiar humans (McCall et al, 1969;Davis et al, 1997).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Such a finding is somewhat surprising considering research from other species has shown that a familiar handler is usually preferred to one that is unfamiliar. For example, cattle are quicker to approach and show decreased flight response to familiar individuals (Breuer et al, 2003) and rats are more likely to choose to have physical contact with a familiar handler (Davis et al, 1997). Furthermore, when considering pet species, dogs have been shown to demonstrate more social approaches when handled by a familiar person, although the familiar person in this case, was not their owner (Kuhne et al, 2012).…”
Section: Influence Of Handler Familiaritymentioning
confidence: 96%